Optimal Strategy for Corporate International Investment and Consumption Problem with Stochastic Hyperbolic Discounting - Jun Long; Sanyun Zeng; Brij B. Gupta; Jindan Zhang; Nadia Nedjah (Journal of Innovation & Knowledge, 2024)
This study investigates the dynamics of a stochastic hyperbolic discounting model in a continuous-time framework to address the complexities associated with the corporate international investment consumption problem (CIICP). By formulating a dynamic programming equation based on the principles of dynamic programming, we seek to untangle the intricacies of CIICP by incorporating log utility. Our research provides valuable insights into the economic ramifications of the proposed model and presents a comprehensive analysis of numerical sensitivities. This investigation not only contributes to a deeper understanding of the CIICP phenomenon but also contributes to more informed decision-making within the field.